Demographic Comparison of American Individuals in Polyamorous and Monogamous Relationships. Issue 6 (24th July 2019) - Balzarini, Rhonda N.; Dharma, Christoffer; Kohut, Taylor; Holmes, Bjarne M.; Campbell, Lorne; Lehmiller, Justin J.; Harman, Jennifer J.
Abstract : Research on polyamorous relationships has increased substantially over the past decade. This work has documented how polyamory is practiced and why individuals might pursue such arrangements. However, there is a lack of a systematic investigation of who is in polyamorous relationships and how they might differ from individuals in monogamous relationships. The present study is one of the first to address this by comparing the demographic backgrounds of individuals in polyamorous ( N  = 2, 428) and monogamous ( N  = 539) relationships in the United States. Compared to participants in monogamous relationships, those in polyamorous relationships were more likely to report minority sexual identities. Despite similar age distributions, individuals in polyamorous relationships were more likely to report being in a civil union, being divorced, and earning less than $40, 000 per year compared to individuals in monogamous relationships. People in polyamorous relationships were also more likely to select "other" options for most demographic characteristics, suggesting that they tend to choose less traditional response options in general. The current research highlights several demographic differences that need to be considered and potentially controlled for in future comparisons of polyamorous and monogamous relationships.